Aplikasi Urin Kelinci pada Tanaman Selada Merah (Lactuca sativa varietas Red rapids). - Nindapinta Dian Wijayanti (JURNAL VIGOR, 2025)
The aim of this research is to determine the effect of rabbit urine concentration and frequency on yield of red lettuce. The research was carried out in March to April 2022 at Sidorejo Village, Bandongan District, Magelang Regency with latosol soil type. The research used a factorial (4x3) experiment arranged in a randomized completely blok design with 3 replications. The first factor is the concentration of rabbit urine 10, 20, 30 and 40 ml/l. The second factor is frequency of rabbit urine application wich is 3, 6 and once every 9 days. The results showed that rabbit urine concentration of 40 ml/l resulting in the highest fresh weight of root. The frequency of rabbit urine application the same growth in the number of leaves, leaf area, fresh weight of plant, dry weight of plant and dry weight of root. The concentration and frequency of rabbit urine application the same growth in all observed parameters.